Imotilisasi, Kadar Glukosa dan Sintasan Ikan Nila (Oreochromis sp) Dalam Larutan Infusum Daun Durian (Durio zibethinus) - Taufik Budhi Pramono; Anandita Ekasanti; Sri Marnani; R Panji Sulaeman (Universitas Batangahari Jambi, 2022)
Durian leaves have been used extensively to aid in the anesthetic process in various types of fish. The purpose of this study was to determine the immotilization capacity and stress response and survival of Tilapia under anesthesia. The RAL study design (4x4) was carried out with the durian leaf infusion treatment at concentrations of 2%, 4%, 6% and 8%. The fastest induction and sedation times were at 8% and 6% concentrations, which were 12.33 minutes and 13.35 minutes, respectively. The highest survival rate was at a concentration of 2% which reached 100%. Blood glucose levels increased due to anesthesia, ranging from 67.75 to 134.25 mg/dL